2021
DOI: 10.3390/ijms22094900
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Pathogenesis of Systemic Mastocytosis

Abstract: Mastocytosis is a type of myeloid neoplasm characterized by the clonal, neoplastic proliferation of morphologically and immunophenotypically abnormal mast cells that infiltrate one or more organ systems. Systemic mastocytosis (SM) is a more aggressive variant of mastocytosis with extracutaneous involvement, which might be associated with multi-organ dysfunction or failure and shortened survival. Over 80% of patients with SM carry the KIT D816V mutation. However, the KIT D816V mutation serves as a weak oncogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 88 publications
0
11
0
2
Order By: Relevance
“…3 Because of its close association with KIT D816V (>90% detection rate with polymerase chain reaction-based peripheral blood test), 12 it was reasonable to consider disease-causing or phenotype-patterning implications and thus pursue KIT-targeted therapies. 2,13,14 Accordingly, midostaurin (a KIT-inclusive multi-kinase inhibitor) and avapritinib (a specific KIT D816V inhibitor) have undergone early phase non-randomised trials and have shown palliative activity in both adv-SM and ISM, which was underwhelming in terms of mustering complete and durable morphological and molecular remissions. 11,15 The particular scenario is similar to what has been the case in Janus kinase 2 (JAK2)-directed therapy in myeloproliferative neoplasms, where JAK2 inhibitors have been effective in alleviating symptoms and splenomegaly, but have fallen short in terms of producing morphological or molecular remissions.…”
Section: Discussionmentioning
confidence: 99%
“…3 Because of its close association with KIT D816V (>90% detection rate with polymerase chain reaction-based peripheral blood test), 12 it was reasonable to consider disease-causing or phenotype-patterning implications and thus pursue KIT-targeted therapies. 2,13,14 Accordingly, midostaurin (a KIT-inclusive multi-kinase inhibitor) and avapritinib (a specific KIT D816V inhibitor) have undergone early phase non-randomised trials and have shown palliative activity in both adv-SM and ISM, which was underwhelming in terms of mustering complete and durable morphological and molecular remissions. 11,15 The particular scenario is similar to what has been the case in Janus kinase 2 (JAK2)-directed therapy in myeloproliferative neoplasms, where JAK2 inhibitors have been effective in alleviating symptoms and splenomegaly, but have fallen short in terms of producing morphological or molecular remissions.…”
Section: Discussionmentioning
confidence: 99%
“…The latter include clonal mast cell activations disorders/CMCAS (also referred to as monoclonal mast cell activation syndromes/MMAS), mast cell activation secondary to allergic, inflammatory, or paraneoplastic disease, and idiopathic disorders [ 16 , 22 , 25 , 26 , 27 , 28 ]. These conditions have been better understood by the medical community in the last few decades due to advances in cellular biology and molecular techniques, leading to improved attempts at classification and prognostication [ 15 , 29 , 30 , 31 ]. A commonly observed gain of function mutation seen (KIT D816V) is a somatic missense A to T mutation and involves substitution of aspartic acid (D) to valine (V) at amino acid 816 in exon 17 of the KIT gene (a proto-oncogene also referred to as c-KIT), which encodes the KIT protein (CD117 or stem cell factor receptor/SCFR), a receptor tyrosine kinase.…”
Section: Introductionmentioning
confidence: 99%
“…Men were found to be more prone to the KIT D816V mutation and were more likely to acquire advanced forms of SM, translating to worse overall survival (OS) and progression-free survival (PFS) [ 13 ]. A small minority of AdvSM cases have also been associated with the V560G, D815K, D816Y, D816F, D816H, and D820G mutations in the KIT gene [ 14 - 19 ]. Longley et al have suggested that KIT mutations affect the regulation of the kinase molecule and alter certain amino acids within the enzymatic domain of the tyrosine kinase [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…Longley et al have suggested that KIT mutations affect the regulation of the kinase molecule and alter certain amino acids within the enzymatic domain of the tyrosine kinase [ 20 ]. Although KIT mutations are thought to be crucial in the development of SM, it is postulated that mutations in other genes, such as TET2, SRSF2, RUNX1 and ASXL1, are also required for SM to develop [ 13 , 14 , 21 - 23 ].…”
Section: Reviewmentioning
confidence: 99%